Perwujudan Entitas dan Identitas Bangsa Indonesia Pada Pendidikan Abad 21 Melalui Penerapan Profil Pelajar Pancasila di SMA Negeri 14 Medan - Theresia Safitri; Liesna Andriany (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research discusses the Realization of the Entity and Identity of the Indonesian Nation in 21st Century Education through the Implementation of the Pancasila Student Profile at SMA Negeri 14 Medan. This research was conducted at SMA Negeri 14 Medan. This research uses qualitative research with a qualitative approach while the data collection carried out is observation, interviews and documentation. This research shows that the realization of the entity and identity of the Indonesian nation in 21st century education through the implementation of the Pancasila student profile at SMA Negeri 14 Medan has been running effectively. This can be seen in the activities carried out by students in implementing the embodiment of the Pancasila student profile in accordance with 6, namely the Pancasila Student Profile, which is a formulation of the ideals of national education, namely having noble character, independence, critical reasoning, creativity, mutual cooperation and global diversity.